Association of safety climate with safety performance in pre-hospital emergency health services - Oruç, Mehmet; Gümüş, Rojan (Frontiers in Public Health, 2025)
AimPre-hospital emergency healthcare workers are often the first responders to critical events. In these situations, they often struggle to comply with safety measures, as they have limited time to save lives while simultaneously ensuring their safety, as well as that of their colleagues and patients. This study aimed to discover the relationship between safety climate and safety performance among pre-hospital emergency healthcare workers.MethodsThe study data were collected from 464 volunteer employees through face-to-face interviews using a personal information form, the Safety Climate Scale, and the Safety Performance Scale. The study performed descriptive statistics, ANOVA, Scheffe tests, student’s t-test, regression, and path analyses. It also performed exploratory and confirmatory factor analysis, Cronbach’s alpha, and Skewness and Kurtosis.ResultsAccording to the results of the study, safety climate (SC) was positively related to the safety performance (SP) of the workers (β = 0.480; p < 0.001). Those with low safety performance averages were exposed to more violence (F = 3.310; p < 0.05) and had more occupational diseases (F = 2.979; p < 0.05) and occupational accidents (F = 5.002; p < 0.001). While there was no difference in safety climate and safety performance scores between groups in terms of gender and marital status, SC and SP were higher in more educated, older, and higher-income groups. The factors most positively related to SP of employees included awareness and competence (β = 0.300; p < 0.001), safety communication (β = 0.207; p < 0.001), and safety training (β = 0.163; p < 0.001). On the other hand, the organizational environment subdimension of SC was negatively associated with safety performance (β = −0.150; p < 0.001). As the safe environment in the workplace diminished due to time pressures and uncontrolled scenes, pre-hospital emergency healthcare workers took control and exhibited safer behaviors.ConclusionThe study findings showed that increased safety climate in the workplace plays an important role in employees’ safe behaviors. Based on these findings, working hours of employees should be regulated; staff numbers, safety training, and safety communication should be increased; and physical conditions should be improved in pre-hospital emergency healthcare.